2013
DOI: 10.2147/ijwh.s45815
|View full text |Cite
|
Sign up to set email alerts
|

Perception on prevention of mother-to-child-transmission (PMTCT) of HIV among women of reproductive age group in Osogbo, Southwestern Nigeria

Abstract: IntroductionThe fastest growing group of adults living with human immunodeficiency virus (HIV), is women. As more women contract the virus, the number of children infected in utero, intra-partum, and during breastfeeding has been growing. This study assessed the knowledge and attitude of women of child bearing age towards the prevention of mother-to-child-transmission (PMTCT) of HIV.Materials and methodsThis is a descriptive cross sectional survey of 420 women of the reproductive age group (15–49 years) select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 25 publications
6
22
2
Order By: Relevance
“…This study have showed that most of the respondents, 229 (97.10%), would agree to VCT, and only 7 (2.9%) would not agree. This result is similar with that of south western Nigeria which has showed that Most of the respondents, 349 (83.10%), would agree to VCT, 36 (8.60%) would not agree, while 35 (8.30%) were not sure [18,21,22].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study have showed that most of the respondents, 229 (97.10%), would agree to VCT, and only 7 (2.9%) would not agree. This result is similar with that of south western Nigeria which has showed that Most of the respondents, 349 (83.10%), would agree to VCT, 36 (8.60%) would not agree, while 35 (8.30%) were not sure [18,21,22].…”
Section: Discussionsupporting
confidence: 86%
“…Pre-tested structured questionnaire was prepared by reviewing previously done studies on the topic of interest [19][20][21][22][23][24][25]. The data were collected using structured interviewer administered questionnaire prepared to address knowledge, attitude, practice associated with PMTCT services.…”
Section: Data Collectionmentioning
confidence: 99%
“…This tendency has been observed throughout Brazil by the increased number of newborns exposed to the risk of HIV [1][2][3] . The first cases of AIDS in children were recorded in 1982 by Ammann and O'Reilly, who reported cases of vertical transmission of HIV from the infected mother to child.…”
Section: Introductionmentioning
confidence: 85%
“…Most children acquire the virus from their mothers through vertical transmission, which compromises their immune system in the fullness of its growth 6 . Vertical transmission can occur in the uterus at anytime during pregnancy, during normal or cesarean delivery, or via breastfeeding [1][2][3]5 . Significant functional abnormalities due to HIV infection make children more susceptible to opportunistic infections, including those in the oral cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Mother-To-Child Transmission (MTCT) accounts for the vast majority of more than 700,000 estimated new HIV infections in children worldwide annually [1]. Every day, more than 1800 babies contract HIV from their mothers worldwide; and many of these cases occur in Africa [2].…”
Section: Introductionmentioning
confidence: 99%